PENGEMBANGAN LEMBAR KERJA SISWA BIOLOGI SMA/MA KELAS X DENGAN KONTEN KECERDASAN EMOSIONAL PADA MATERI PERUBAHAN DAN PELESTARIAN LINGKUNGAN UNTUK MENINGKATKAN HIGHER ORDER THINKING SKILLS (HOTS) - Encik Rosiana Encik Rosiana; Evi Suryawati Evi Suryawati; Nursal ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research aimed to develop LKS SMA / MA grade X with emotional intelligence content in the material change and environmental preservation to improve HOTS. Research conducted at the Laboratory of Biology PMIPA FKIP Riau and MAN 2 Model Pekanbaru in March-June 2015.The research procedures are adapted from the R and D (Research and Development) with ADDIE model development, the procedures includes: Analyze, Design, Development, implementation and Evaluation. This research was carried out until the stage of development. Data collection instruments used validation sheets and students response questionnaire. Limited trials conducted to look at the feasibility worksheets that have been developed. The data obtained were analyzed to determine the validity of student worksheet. The tryout subjects in this research are 26 students of X Science 7 class in MAN 2 Model Pekanbaru. The subject in the research is KD 3.10 on the environmental balance, waste handling, fertilizer Bokashi and damage caused by pollution. The products content has been revised based on the result of the field test (tryout II) and the suggestions from the validators.The validation results namely (1) student worksheet 1: balance environmental, 3,25 with a valid category; (2) student worksheet 2: waste management 3,30, with the category of very valid; (3) LKS Bokashi fertilizer 3,16 with a valid category; (4) LKS 4: damage caused by pollution is 3,05 with a valid category. The overall response of students to the LKS is very good. Based on the results of data analysis showed that development of biology students worksheet SMA/MA grade x in change and environmental preservations chapter with emotional intelligence content to improve the student’s higher order thinking skills (HOTS) potentially as a source in the learning process and it can be used with a mean of valid criteria.Keywords: Biology Student Worksheet, Emotional Intelligence, HOTS